Empirical studies on the effect of electromagnetic radiation from multiple sources in Dhaka - Munima Haque; Mohammad Quamruzzaman; Shohag Hossain; S. M. Sahidur Rahaman (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
Just after the invention of electricity by Michael Faraday, there has been a revolution in the communication technology, which lead to the invention of radio, television, radar, satellite, and mobile. While these machines transformed our life high quality, safer and simpler, they have been associated with alarming probable health hazards owing to their electromagnetic radiation (EMR) emission. Couple of cases it has been reported by personals regarding various health related issues relating to exposure on electromagnetic field (EMF) and EMR. Although couple of persons showed light symptoms and respond by avoiding the electrical field (EF) and EMR fields as much as possible, some others are so much affected that they have changed their entire lifestyle. In this paper, empirical survey study has been carried out in the laboratories of Daffodil International University (DIU) main and permanent campus. It was found that some of the instrument had higher EMFs. The findings from this survey may be helpful for the students to take precautionary measurement who work for long duration in the various laboratories for their practical classes and for the users of the domestic appliances as well as office equipment and industrial instruments.